One-step zero-background IgG reformatting of phage-displayed antibody fragments enabling rapid and high-throughput lead identification. Issue 4 (16th November 2013) - Chen, Chao-Guang; Fabri, Louis J.; Wilson, Michael J.; Panousis, Con
Abstract: We describe a novel cloning method, referred to as insert-tagged (InTag) positive selection, for the rapid one-step reformatting of phage-displayed antibody fragments to full-length immunoglobulin Gs (IgGs). InTag positive selection enables recombinant clones of interest to be directly selected without cloning background, bypassing the laborious process of plating out cultures and colony screening and enabling the cloning procedure to be automated and performed in a high-throughput format. This removes a significant bottleneck in the functional screening of phage-derived antibody candidates and enables a large number of clones to be directly reformatted into IgG without the intermediate step of Escherichia coli expression and testing of soluble antibody fragments. The use of InTag positive selection with the Dyax Fab-on-phage antibody library is demonstrated, and optimized methods for the small-scale transient expression of IgGs at high levels are described. InTag positive selection cloning has the potential for wide application in high-throughput DNA cloning involving multiple inserts, markedly improving the speed and quality of selections from protein libraries.